2007
DOI: 10.1029/2006gl027666
|View full text |Cite
|
Sign up to set email alerts
|

A coupling function for solar wind effect on geomagnetic activity

Abstract: [1] From a simple theoretical consideration, we obtained two coupling functions linking upstream solar wind parameters to geomagnetic activity. We took into account (1) a scaling factor related to polar cap expansion while increasing the reconnected magnetic flux in the dayside magnetosphere, and (2) a modified Akasofu function for the reconnected flux for combined IMF B z and B y components. One of these coupling functions may be written as F a = aV sw B yz 1/2 sin a (q/2), where V sw is the solar wind speed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…These values are close to those reported by Slavin et al (2009) who found the normal magnetic field to the magnetopause during the second MESSEN-GER flyby of $13 nT and the cross-magnetospheric electric field E 1 % 2 mV/m (see also Blomberg et al, 2006). Taking into account a significant contribution to the magnetospheric convection from IMF B y component (e.g., Lyatsky et al, 2007, the references therein), we obtain the average electric field in the Mercury's magnetosphere some higher, say E 1 % 5 mV/m. Due to convergence of the magnetic field lines, the electric field E 1 near the Mercury's surface may be two-three times stronger.…”
Section: Application Of the Awr Model To Mercurysupporting
confidence: 88%
“…These values are close to those reported by Slavin et al (2009) who found the normal magnetic field to the magnetopause during the second MESSEN-GER flyby of $13 nT and the cross-magnetospheric electric field E 1 % 2 mV/m (see also Blomberg et al, 2006). Taking into account a significant contribution to the magnetospheric convection from IMF B y component (e.g., Lyatsky et al, 2007, the references therein), we obtain the average electric field in the Mercury's magnetosphere some higher, say E 1 % 5 mV/m. Due to convergence of the magnetic field lines, the electric field E 1 near the Mercury's surface may be two-three times stronger.…”
Section: Application Of the Awr Model To Mercurysupporting
confidence: 88%
“…A detailed description of our approach in analyzing these events is presented by MacNeice [2009]. A number of studies [ Lyatsky et al , 2007; Perreault and Akasofu , 1978] have shown that the geomagnetic disturbance on the ground in the dayside polar cap region is well correlated with the product of the solar wind speed and the southward component of the interplanetary magnetic field (IMF). Neither the WSA model, or the heliospheric MHD models adequately forecast the southward component of the IMF.…”
Section: Introductionmentioning
confidence: 99%
“…[7] For calculation of the polar magnetic (PM) index, we used the Akasofu function [Perreault and Akasofu, 1978;Akasofu, 1981; see also Lyatsky et al, 2007, and references therein]…”
Section: Methods Of Calculation Of the Polar Magnetic Index And Data Umentioning
confidence: 99%
“…Lyatsky et al [2007] proposed a coupling function, obtained from a simple theoretical consideration and linking upstream solar wind data to geomagnetic activity. They used the Perreault-Akasofu method [Perreault and Akasofu, 1978] and took into account a scaling factor due to polar cap expansion while increasing a reconnected magnetic flux in the dayside magnetosphere.…”
Section: Coupling Function 31 Deriving the Appropriate Coupling Funmentioning
confidence: 99%